Digital video recorder dodgers – Sport-viewing habits in the face of changing media reality. (November 2019) - Tamir, Ilan
In an era in which viewers can record television content to be watched at any time of convenience using a variety of broadcast media, delayed viewing has emerged as a self-evident and natural option for many content-consumers. An interesting exception to this trend, however, is sport – football, in particular – which supporters insist on watching exclusively in real-time. The present study has sought to understand the obsessive dedication of sports fans with watching sport content only in real-time. This peculiar insistence results in the viewer giving up some rather useful technological amenities. Through in-depth interviews conducted with 34 soccer fans, this study aimed to explore the apparent and adamant fan refusal to "delay gratification" – that is, only watching broadcast sport content in real-time. The interview analysis offers some salient explanations for the phenomenon. For example, football fans self-identify as members of a community in a quasi-religious sense, deeply committed to rules and ceremonies to be ritualistically performed at appropriate and specific times. Indeed, to exceed these rules is to violate the norms of the community. Many fans also believe they can somehow influence the match and its outcome by their viewing presence, and must, therefore, be in front of the screen in real-time. In fact, the bond between fan and team is analogous to a relationship characterized by deep and intimate emotions. This bond can be stretched by any fan who is absent from the real-time screen-viewing experience of the sporting event, engendering feelings of treachery and betrayal of the fan-team love relationship. The dynamics of this relationship have social, media, and economic implications, as well.